Is “modular” the way to go for small group learning in community medicine in undergraduate clinical postings? - Chavda, Paragkumar (Int J Appl Basic Med Res, 2016)
CONTEXT: There is a need to shift from the didactic lecture-based instruction to more student-centered active learning methods for undergraduate teaching in community medicine. AIMS: To compare didactic and modular method of learning on Level 1 and 2 on Kirkpatrick’s training evaluation model. SETTINGS AND DESIGN: This was a two-arm educational intervention study for a small group of the 2(nd) year MBBS students in their 4(th) semester during clinical posting in the subject of community medicine. SUBJECTS AND METHODS: The topic chosen was “rabies prophylaxis” in the 2(nd) clinical posting during 4(th) semester. With permission from Institutional Ethics Committee, first batch of 17 students was taught this topic by didactic method. Next batch of 22 students was taught by the modular method. A self-reading module was prepared for this study and validated by three teachers. What was different in modular teaching was a circular sitting arrangement, module reading by students, video presentation, and exercise using case vignettes. STATISTICAL ANALYSIS USED: Student’s t-test was used for pre- and post-test score comparison and Mann–Whitney U-test for students' responses on Likert scale. RESULTS: The mean gain in obtained marks after modular learning (7.9/15) was significantly higher as compared to gain after didactic teaching (5.9/15) (P = 0.0038); more students asserted to be confident to manage a case in modular group compared to the didactic group (P < 0.05) indicating a higher level of learning through modular teaching. CONCLUSIONS: Modular teaching fares better than didactic method and hence should be used more frequently in community medicine clinical posting.